Pendekatan Komunikasi Keluarga di Kabupaten Magetan untuk Mencegah Dampak Negatif Media Sosial bagi Anak di Bawah Umur - Veny Ari Sejati (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2013)
The crime rate in the form of sexual abuse mostly originated from Internet. In one year there were 80 cases and most of the victims were students of private schools and still underage. This study aims to gain an authentic understanding of the experience of people, as perceived by the people concerned. This study used qualitative approach. The results indicates that one of the approaches used by the family in preventing negative effects of social media is interpersonal communication approach (face to face). Face to face communication has specialty in which the effects and feedback, action and reaction directly visible because of physical distance of participants. Actions and reactions to verbal and non-verbal, everything looks clear in direct manner.